2016
DOI: 10.1016/j.bpj.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Regulation and Time Hierarchy of Oxidative Phosphorylation in Cardiac Mitochondria

Abstract: To determine how oxidative ATP synthesis is regulated in the heart, the responses of cardiac mitochondria oxidizing pyruvate to alterations in [ATP], [ADP], and inorganic phosphate ([Pi]) were characterized over a range of steady-state levels of extramitochondrial [ATP], [ADP], and [Pi]. Evolution of the steady states of the measured variables with the flux of respiration shows that: (1) a higher phosphorylation potential is achieved by mitochondria at higher [Pi] for a given flux of respiration; (2) the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 46 publications
1
31
1
Order By: Relevance
“…Most recently Vinnakota et al . ( a ) reported that P i did not modulate the activity of Complex III in isolated mitochondria, in conflict with a previous report by Bose et al . (2013).…”
Section: Discussioncontrasting
confidence: 78%
“…Most recently Vinnakota et al . ( a ) reported that P i did not modulate the activity of Complex III in isolated mitochondria, in conflict with a previous report by Bose et al . (2013).…”
Section: Discussioncontrasting
confidence: 78%
“…High‐resolution respirometry determines mitochondrial function by measuring mitochondrial oxygen consumption after a bolus injection of ADP. Since the experiment is performed in a sealed chamber, all oxygen consumed after a bolus of ADP is directly related to the production of ATP through complex IV of the mitochondrial respiratory chain . While this measure is performed in non‐physiological conditions (ie, saturating O 2 ), it permits comparison of maximal aerobic function without confounding influences present in the cellular environment.…”
Section: Mitochondrial Function and Skeletal Muscle Metabolism In Metmentioning
confidence: 99%
“…Hence, in the simulations, when O 2 is zero and the respiratory chain is blocked, NAD becomes highly reduced but not to 100%, due to the reversibility of DH. (b) In experimental measurements, the signal of NAD in the presence of an inhibitor of the respiratory chain or in anoxia is assigned to 100% reduction (e.g., ), although NADH is also used by other reactions.…”
Section: Resultsmentioning
confidence: 99%
“…However recently, Vinnakota challenged the Pi activation with an indirect experimental approach, and Chess et al . could disprove the particular mechanism (crossover of reduction states within complex III) proposed by Bose et al .…”
Section: Discussionmentioning
confidence: 99%